ENSURING THE EUROPEAN STANDARDS OF THE QUALITY OF HIGHER PHARMACEUTICAL EDUCATION AT THE INSTITUTIONAL LEVEL - Рева, Т. Д. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article reveals best practices in ensuring the highest European standards of the quality of pharmaceutical education in Ukraine at the institutional level; it consolidates the European experience of tertiary education quality assurance; it provides insights into the current issues of ensuring European standards of higher pharmaceutical education in Ukraine at the institutional level; it highlights practical results of the quality assessment of higher pharmaceutical education with regard to the example of professional expertise of test materials of licensing examination «Krok 1. Pharmacy» at the National Medical University named after A. A. Bogomolets